THE EFFECTIVENESS OF HANDS-ONLY OFFLINE APPLICATION - Fatimah Khoirini; Misniarti Misniarti (Proceeding B-ICON, 2022)
Cardiac arrest is an emergency that can occur inside or outside the hospital and has a high risk of death. However, the survival rate is higher if cardiopulmonary resuscitation (CPR) first aid is given immediately. The patient’s family can give first aid in the form of hands-only CPR if the cardiac arrest incident occurs at home. Nowadays, learning to use hands-only CPR offline application on a mobile phone is one way to increase knowledge and skills besides being easy to access, we can also take it with us wherever we go. This study aims to determine whether hands-only cardiac resuscitation offline applications can improve family skills. This study was quasi-experimental, using a control group with pre-test and post-test designs. The experimental group used independent learning through a hands-only CPR offline application, while the control group used a hands-only CPR simulation. The number of samples for each group was 17 people, with a total of 34 people for the two groups. Analysis was done using Wilcoxon and Mann-Whitney. P-value obtained was 0.000, so there is a significant difference in CPR skills before and after intervention in the offline application group and the simulation group. P-value obtained was 0.000, so there is a significant relationship between offline application and simulation in improving the skills of patients’ families in performing hands-only CPR. Learning through a CPR hand-only application improves the skills of the family of patients with heart disease to perform hands-only CPR. Meanwhile, learning with a simulation method has a higher rank in improving the skills of the family of patients with heart disease to perform hands-only CPR.